PENGGUNAAN METODE PERMAINAN KARTESIUS DALAM MENINGKATKAN PENGETAHUAN DASAR IPA SISWA MADRASAH IBTIDAIYAH AL-FALAH KABUPATEN GORONTALO - Napu, Dewi Darmiyani; Mohamad, Sabrina Nadjib; Akolo, Ingka Rizkyani; Sarif, Suharia (Al-Mulk: Jurnal Pengabdian Masyarakat, 2024)
One of the method that can be used for science learning in elementary schools is educational game. Through games we can create ideal conditions for learning and improve the quality of learning. This service activity uses Cartesian games as a learning medium. This activity was carried out at Madrasah Al-Falah, Gorontalo district. The results of the service activities show that the use of the Cartesian game method is very effective in increasing children's basic science knowledge and they can have an enjoyable learning experience.Keywords: Game Methode; Cartesius ; Sains.